What Really Drives Firm Value? A Systematic Literature Review of Firm Size, Corporate Governance, and Capital Structure - Zebua, Wistiani; Djaddang, Syahril; Merawati, Endang Etty (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
In a competitive and dynamic business world, company value is one of the main indicators that reflects the success of management in managing company resources and strategies. The purpose on this literature review study is determine and analyze the simultaneous and partial effects of company size, capital structure, and corporate governance on company value. This scientific article was written using qualitative methods and library research. The results of this study indicate that company size does not affect company value, while capital structure and corporate governance do affect company value. A large company size will be a positive signal for investors if it is balanced with stable and measurable performance. Capital structure can be healthy with a proportional debt composition signals management's confidence in the company's ability to manage risk and generate profits. Similarly, the implementation of transparent, accountable, and professional corporate governance signals to investors that the company is well-managed and trustworthy.